Evaluating the effectiveness of English language learning supported by artificial intelligence: A Survey at Hong Bang International University - Thao, Nguyen Thi Bich (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
The purpose of this study is to determine whether chatbots are likely to improve Hong Bang International University students' English language proficiency. A survey was conducted to investigate 229 English majors' opinions and experiences with chatbots. The results showed the advantages as well as disadvantages of using chatbots. Most of the students like using chatbots since chatbots provide quick feedback, are mobile-friendly and offer conversation and grammar practice. Nevertheless, difficulties in managing complicated language and guaranteeing information authenticity surfaced. Furthermore, restrictions in advanced grammar practice were found. According to the study, chatbots can be useful resources, especially for cultivating fundamental skills and getting quick feedback. Ultimately, the study highlights that chatbots can supplement conventional techniques and human interaction, not replace traditional methods and human interaction for comprehensive language acquisition. In short, the study emphasizes the importance of taking accessibility into account when including chatbots as tools for language acquisition.